2019
DOI: 10.1371/journal.pgen.1008149
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis identifies a natural variation in basic helix-loop-helix transcription factor regulating ascorbate biosynthesis via D-mannose/L-galactose pathway in tomato

Abstract: Tomato ( Solanum lycopersicum ) is one of the highest-value vegetable crops worldwide. Understanding the genetic regulation of primary metabolite levels can inform efforts aimed toward improving the nutrition of commercial tomato cultivars, while maintaining key traits such as yield and stress tolerance. We identified 388 suggestive association loci (including 126 significant loci) for 92 metabolic traits including nutrition and flavor-related loci by genome-wide association study from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 67 publications
(87 reference statements)
1
53
1
Order By: Relevance
“…The mutation results in unbranched inflorescences with exceptionally large sepals 32 . An 8-bp insertion in the promoter of SlbHLH59 significantly increased its expression in accessions producing high ascorbic acid levels 37 . In apple (Malus × domestica), multiple repeats of a 23-bp motif in the promoter of MYB10 generate an autoregulatory locus, which is sufficient to account for increased expression and ectopic accumulation of anthocyanins in red-fleshed apples 38 .…”
Section: Insertionsmentioning
confidence: 99%
“…The mutation results in unbranched inflorescences with exceptionally large sepals 32 . An 8-bp insertion in the promoter of SlbHLH59 significantly increased its expression in accessions producing high ascorbic acid levels 37 . In apple (Malus × domestica), multiple repeats of a 23-bp motif in the promoter of MYB10 generate an autoregulatory locus, which is sufficient to account for increased expression and ectopic accumulation of anthocyanins in red-fleshed apples 38 .…”
Section: Insertionsmentioning
confidence: 99%
“…The tomato basic helix-loop-helix 59 (bHLH59) gene was recently identified as the likely candidate underlying the ascorbate quantitative trait locus TFA9 in tomato [110]. The bHLH59 transcription factor positively regulates the transcription of genes of the L-galactose pathway, including PMI, PMM, GMP1, GMP2, GMP3, GMP4, and GME1 [110]. Knock-down of the bHLH59 gene with RNAi in tomato reduced ascorbate to 65% of wild-type levels [110].…”
Section: Basic Helix-loop-helix 59 Transcription Factor (Bhlh59)mentioning
confidence: 99%
“…The bHLH59 transcription factor positively regulates the transcription of genes of the L-galactose pathway, including PMI, PMM, GMP1, GMP2, GMP3, GMP4, and GME1 [110]. Knock-down of the bHLH59 gene with RNAi in tomato reduced ascorbate to 65% of wild-type levels [110]. Increased expression of the bHLH59 gene in tomato increased ascorbate concentrations 1.5-fold and was associated with enhanced tolerance to methyl viologen-induced stress [110] (Table 3).…”
Section: Basic Helix-loop-helix 59 Transcription Factor (Bhlh59)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, implementing genome wide association study (GWAS) on 302 tomato accessions identified a basic helix-loop-helix (bHLH) transcription factor, SlbHLH59, which positively regulates ascorbate content in tomato fruits [78]. The most similar protein to SlbHLH59 in Arabidopsis appears to be unfertilized embryo sac 12 (UNE12), regulating fertilization [78]. Further investigations are, however, needed to clarify whether this protein has links to the accumulation of ascorbate in Arabidopsis.…”
Section: Transcriptional Regulationmentioning
confidence: 99%